2020
DOI: 10.1002/pbc.28268
|View full text |Cite
|
Sign up to set email alerts
|

The association between timely opioid administration and hospitalization in children with sickle cell disease presenting to the emergency department in acute pain

Abstract: Introduction The National Heart, Lung, and Blood Institute guidelines for sickle cell disease (SCD) pain crisis management recommend opioids within 60 minutes of emergency department (ED) registration and every 30 minutes thereafter until acute pain is managed. These guidelines are based on expert opinion without published, supporting data. Objective To evaluate the association between timely ED opioid administration and hospitalization rates in children with SCD. Methods Retrospective cohort of children prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Our findings support the observation by Kavanagh and colleagues that demonstrated a 32%–48% increase in the proportion of children with SCD‐VOE who were discharged from the ED in a quality improvement initiative that focused on an initial dose of intranasal fentanyl, standardizing care, implementing a pain medication calculator, and education of providers and caregivers 12 . Akinsola and colleagues found a significantly higher discharge rate in patients receiving intranasal fentanyl compared to those receiving IV opioids only (48% vs. 71%, p = .004) in a prospective quality improvement initiative, 10 while results from other single center studies have differed 4,15 . It is possible that the other interventions in the study by Kavanagh et al may have also contributed to greater rates of ED discharge and not the intranasal fentanyl alone.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings support the observation by Kavanagh and colleagues that demonstrated a 32%–48% increase in the proportion of children with SCD‐VOE who were discharged from the ED in a quality improvement initiative that focused on an initial dose of intranasal fentanyl, standardizing care, implementing a pain medication calculator, and education of providers and caregivers 12 . Akinsola and colleagues found a significantly higher discharge rate in patients receiving intranasal fentanyl compared to those receiving IV opioids only (48% vs. 71%, p = .004) in a prospective quality improvement initiative, 10 while results from other single center studies have differed 4,15 . It is possible that the other interventions in the study by Kavanagh et al may have also contributed to greater rates of ED discharge and not the intranasal fentanyl alone.…”
Section: Discussionsupporting
confidence: 89%
“…12 Akinsola and colleagues found a significantly higher discharge rate in patients receiving intranasal fentanyl compared to those receiving IV opioids only (48% vs. 71%, p = .004) in a prospective quality improvement initiative, 10 while results from other single center studies have differed. 4,15 It is possible that the other interventions in the study by Kavanagh et al may have also contributed to greater rates of ED discharge and not the intranasal fentanyl alone. However, the use of a population from 20 sites in the United States and Canada adds further evidence in support of the use of intranasal fentanyl.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Consistent with the goal of improved ED care decreasing hospitalizations, a single-site study showed guideline-adherent care decreased hospitalization for children experiencing acute pain episodes. 14 While current research indicates ED care is delayed 15,16 and many individuals with SCD are not satisfied with the care they receive, 17,18 there are no data regarding post-ED care quality. However, if guideline-adherent ED care is provided and results in decreased hospitalization, it is essential to determine if this care results in more patients returning to the ED after being discharged home.…”
Section: Introductionmentioning
confidence: 99%